Atrazine and Diuron Effects on Survival, Embryo Development, and Behavior in Larvae and Adult Zebrafish - Zaluski, Amanda B.; Wiprich, Melissa T.; de Almeida, Luiza F.; de Azevedo, Andressa P.; Bonan, Carla D.; Vianna, Monica R. M. (Frontiers in Pharmacology, 2022)
Atrazine and Diuron are widely used herbicides. The use of pesticides can cause contamination of the aquatic environment, threatening biodiversity and non-target organisms such as fish. In this study, we investigated the effects of acute exposure for 96 hours to atrazine and diuron commercial formulations in zebrafish (Danio rerio, wild-type AB) embryos and larvae, and in adult stages. We observed a significant concentration-dependent survival decrease and hatching delays in animals exposed to both herbicides and on the frequency of malformations compared to the control groups. Morphological defects included cardiac edema, tail reduction and head malformation. At 7 days post fertilization (dpf), atrazine exposure resulted in a reduction in head length at 2, 2.5 and 5 mg/L and increased ocular distance at 1, 2, 2.5 and 5mg/L atrazine when compared to controls. At the same age, diuron increased ocular distance in animals exposed to diuron (1.0 and 1.5 mg/L) and no effects were observed on head length. We also evaluated a behavioral repertoire on larvae at 7 dpf and there no were significant differences in distance traveled, mean speed, time in movement and thigmotaxis for atrazine and diuron when animals were individually placed in a new environment. Larvae cognitive ability was tested at 7dpf for avoidance and optomotor responses and atrazine nor diuron had significant impacts when treated groups were compared to their corresponding controls. Adults’ behavior was evaluated 7 and 8 days after the end of the acute herbicide exposure. Exploration of a new environment and associated anxiety-like parameters, social interaction, and aggressiveness were not altered. Our results highlight the need for further studies on the sublethal effects of both herbicides and the consideration of the effects of commercial formulas versus isolated active ingredients. It also emphasizes the need to take sublethal effects into consideration when establishing residues environmental limits.